Proceedings of the 28th International Conference on Computational Linguistics: Industry Track 2020
DOI: 10.18653/v1/2020.coling-industry.22
|View full text |Cite
|
Sign up to set email alerts
|

Regularized Graph Convolutional Networks for Short Text Classification

Abstract: Short text classification is a fundamental problem in natural language processing, social network analysis, and e-commerce. The lack of structure in short text sequences limits the success of popular NLP methods based on deep learning. Simpler methods that rely on bag-of-words representations tend to perform on par with complex deep learning methods. To tackle the limitations of textual features in short text, we propose a Graph-regularized Graph Convolution Network (GR-GCN), which augments graph convolution n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…For example, Beery et al (2018) [2] demonstrated a network that accurately recognizes cows in a typical context (e.g., pasture) consistently misclassifies cows in a non-typical context (e.g., beach). Similar heuristics also arise in visual question answering systems [1] and researchers proposed graph generative modeling schemes [13] (inspired by graph convolutional networks [30]) to handle the problem implicitly. In this paper, we study this problem within the Natural Language Inference (NLI): the task of determining whether a premise sentence entails (i.e., implies the truth of) a hypothesis sentence [7,8,4].…”
Section: Introductionmentioning
confidence: 89%
“…For example, Beery et al (2018) [2] demonstrated a network that accurately recognizes cows in a typical context (e.g., pasture) consistently misclassifies cows in a non-typical context (e.g., beach). Similar heuristics also arise in visual question answering systems [1] and researchers proposed graph generative modeling schemes [13] (inspired by graph convolutional networks [30]) to handle the problem implicitly. In this paper, we study this problem within the Natural Language Inference (NLI): the task of determining whether a premise sentence entails (i.e., implies the truth of) a hypothesis sentence [7,8,4].…”
Section: Introductionmentioning
confidence: 89%
“…This model uses the HIN framework to model short texts, which can contain any additional information and capture rich relationships between texts and additional information. Tayal et al [39] proposed a regularized GCN for short text classification that uses extra knowledge between text and labels to enhance short text information. Wang et al [40] modelled the short text dataset as a hierarchical heterogeneous graph consisting of three type graphs which introduce more semantic and syntactic information, and then dynamically learned to facilitate effective label propagation.…”
Section: Short Text Classification Based Gcnmentioning
confidence: 99%
“…This model uses the HIN framework to model short texts, which can contain any additional information and capture rich relationships between texts and additional information. Tayal et al [39] proposed a regularized GCN for short text classification that uses extra knowledge between text and labels to enhance short text information. Wang et al [40] modelled the short text dataset as a hierarchical heterogeneous graph consisting of three type graphs which introduce more semantic and syntactic information, and then dynamically learned to facilitate effective label propagation.…”
Section: Short Text Classification Based Gcnmentioning
confidence: 99%